High School Students with Intellectual Disabilities in the School and Workplace: Multiple Perspectives on Inclusion - Bennett, Sheila; Gallagher, Tiffany (Canadian Journal of Education/Revue canadienne de l’éducation, 2013)
Data collected from three urban high schools in Ontario captures multiple voices in relation to inclusive practices in secondary schools and transitions into community. Twenty-one students with intellectual disabilities (ID), 54 teachers, 26 educational assistants, 7 job coaches, 22 parents, 23 peers and 19 community employers completed surveys examining: beliefs about inclusion, inclusion of students with ID in school/workplace, the impact of inclusion on individuals without disabilities, and support, socialization and friendships of students with ID. Results indicate agreement in relation to positive perceptions of inclusion and the impact on school/workplace. Cases in which consensus was not attained are also discussed.